2010
DOI: 10.1002/cncr.25044
|View full text |Cite
|
Sign up to set email alerts
|

Selecting an optimal staging system for hepatocellular carcinoma

Abstract: BACKGROUND: Selecting an appropriate staging system is crucial to predict the outcome of patients with hepatocellular carcinoma (HCC). The optimal prognostic model for HCC is under intense debate. This study investigated the prognostic ability of the 5 currently used staging systems, Barcelona Clinic Liver Cancer (BCLC), Cancer of the Liver Italian Program (CLIP), Japan Integrated Scoring (JIS) system, tumor-node-metastasis (TNM), and Tokyo score, for HCC. METHODS: Between 2002 and 2008, 1713 prospectively enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 39 publications
4
70
1
Order By: Relevance
“…[30][31][32] A recent study compared the BCLC, CLIP, Tokyo, JIS, and TNM staging systems in 1713 Taiwanese patients, and the CLIP staging system was found to be the best overall for early to advanced HCC, regardless of the treatment strategy; this system was followed by the Tokyo, JIS, BCLC, and TNM systems. 33 Notably, only 46.8% of the patients in this report received curative treatment, which included resection (n ¼ 448), transplantation (n ¼ 4), and locoregional therapy (n ¼ 862).…”
Section: Formentioning
confidence: 82%
“…[30][31][32] A recent study compared the BCLC, CLIP, Tokyo, JIS, and TNM staging systems in 1713 Taiwanese patients, and the CLIP staging system was found to be the best overall for early to advanced HCC, regardless of the treatment strategy; this system was followed by the Tokyo, JIS, BCLC, and TNM systems. 33 Notably, only 46.8% of the patients in this report received curative treatment, which included resection (n ¼ 448), transplantation (n ¼ 4), and locoregional therapy (n ¼ 862).…”
Section: Formentioning
confidence: 82%
“…The CLIP system has been externally validated in Korean [11], Taiwanese [12], French [13], Japanese [29], American [14], German [15] cohorts. However, a study of 4525 patients in Japan had reached opposite conclusions that stratification ability and prognostic predictive power of the JIS score were much better than that of the CLIP score [9].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies comparing staging systems in HCC have revealed different ranking of staging systems [11][12][13][14][15][16][17]. However, these studies included patients with early to advanced stages, or only early to intermediate stage, or only advance stage of HCC, whereas our studied population included patients with intermediate to advanced disease that is not amenable to radical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By tumor morphology the investigators meant percentage of parenchymal involvement (more than or less than 50%) and if these were uninodular, multinodular or extensive tumors. Several subsequent studies with large patient populations have demonstrated its prognostic usefulness, including a recent study from Taiwan that compared this system to four other models in 1713 patients with primary liver cancer (Hsu, 2010;Ueno, 2001). A downside to this system is that its tumor morphology classification is too broad for the current practices of aggressive hepatoma screening in high risk populations.…”
Section: Cancer Of the Liver Italian Program (Clip)mentioning
confidence: 99%